After Hours: Agency and Identity in Toronto’s Do-It-Yourself (DIY) Electronic Music Scene - Sermol, Alexandra (University of Waterloo, 2022)
The architecture of a night - a party lasting until the sun breaks, and the crowd of faces disperse, without a trace. What happens in that one night, however, is part of a much longer story about community growth, where small-scale venues encourage experimentations with identity. Do-It-Yourself (DIY) electronic music events inhabit spaces not zoned for nightclub or venue use, making them technically illegal. Meanwhile, the legal zones for nightclubs are some of Toronto’s most expensive real estate creating a high barrier to entry. Unlike large-scale nightclubs, DIY events enable organisers a high degree of curation, allowing them to define new social rules. Increasing access to DIY venues creates opportunities for underground musicians and artists to practise and perform. Their community-led nature suits smaller establishments with more intimate crowds. Resultantly, the DIY dancefloor becomes a space where queer and equity-seeking guests can participate comfortably, free from judgment and harassment. After Hours centres a series of conversations about the experiences and desires of DIY attendees, referencing events in Montreal, London, Tokyo, Berlin, and Toronto. These conversations are fragments of a larger series of eighteen zines that illustrate the socio-spatial dynamics of DIY spaces for future practitioners. Adding to the growing discourse on safety, identity, and gender in urban nightlife, this thesis explores community-led inhabitation and agency. How can spatial and social scale enhance perceived comfort in nighttime spaces?
Keywords: do-it-yourself (DIY); Toronto; electronic music; nightlife; subculture; gender studies